Severe Generalized Epidermolysis Bullosa Simplex in Two Hong Kong Children due to De Novo Variants in KRT14 and KRT5. (17th April 2020) - Chong, Shuk Ching; Hon, Kam Lun; Scaglia, Fernando; Chow, Chung Mo; Fu, Yu Ming; Chiu, Tor Wo; Leung, Alexander K. C.
Abstract : We report two Hong Kong children with severe generalized epidermolysis bullosa simplex (EBS), the most severe form of EBS, without a family history of EBS. EBS is a rare genodermatosis usually inherited in an autosomal dominant fashion although rare autosomal recessive cases have been reported. Genetic studies in these patients showed that the first case was due to a novel de novo heterozygous variant, c.377T>G (NM_000526.5 (c.377T>G, p.Leu126Arg)) in the KRT14 gene and the second case was due to a rare de novo heterozygous variant c.527A>G (NM_000424.4, c.527A>G, p.Asn176Ser) in the KRT5 gene. To our knowledge, the c.377T>G variant in the KRT14 gene has not been previously reported, and the c.527A>G variant in the KRT5 gene is a rare cause of severe generalized EBS. In severe generalized EBS, infants exhibit severe symptoms at the onset; however, they tend to improve with time. A precise genetic diagnosis in these two cases aided in counseling the families concerning the prognosis in their affected children and the recurrence risk for future pregnancies.